A Note on the Preservative Treatment of Fence- Posts by the Sap-Displacement Method - Tewari, M. C.; Mitra, S. N.; Nagaraja Sharma, M. (Indian Forester, 1967)
In the present paper, results of experiments on the preservative treatment of fenceposts by the sap-displacement method are presented. In this method freshly-cut, debarked posts are treated with water-borne preservatives by placing the butt ends into solutions of the preservatives. The preservative rises through and replaces the sap of the posts by ’wick’ action. This method works out satisfactorily with all water-borne preservatives. The present method appears to be simpler and easier than other sap displacement methods.